INFORMATION ANNOUNCEMENT ABOUT THE NATIONAL SYMPOSIUM «LONG QT SYNDROME» MOSCOW, RUSSIA 22-23 MARCH, 2001 - L. M. Makarov; L. A. Kalinin (Российский кардиологический журнал)
Information announcement about the National Symposium «Long QT Syndrome» Moscow, Russia 22-23 March, 2001.